Individual differences in trait anxiety are associated with gray matter alterations in hypothalamus: Preliminary neuroanatomical evidence. (30th January 2019) - Modi, Shilpi; Thaploo, Divesh; Kumar, Pawan; Khushu, Subash
Highlights: High trait anxiety individuals are 'at risk' of developing affective disorders. We assessed relation between trait anxiety and regional gray matter volumes. Hypothalamic gray matter volumes showed a predictive value for trait anxiety. Findings are similar to that obtained Generalized Anxiety Disorder patients. Study supports the need of preventive interventions in high anxious individuals. Abstract: Trait anxiety is particularly a prone phenotype for the development of anxiety disorders and depression. Studying the neural underpinnings of trait anxiety can further inform our understanding of the etiology of these disorders. To investigate the structural correlates of trait anxiety, high resolution structural images were acquired from 76 right-handed healthy participants and gray matter volumes were extracted from a priori regions of interest (ROIs) that were earlier implicated in anxiety like behaviour (i.e., hippocampus, amygdala, anterior cingulate cortex, thalamus, hypothalamus and prefrontal (dorsolateral, rostrolateral, ventrolateral) cortex. In a partial correlation analysis (with age, gender, and Beck Depression Inventory (BDI) scores as covariates of no interest), trait anxiety was found to be negatively correlated with the gray matter volume of hypothalamus bilaterally and positively correlated with the gray matter volume of left thalamus. In a hierarchical multiple regression analysis, grey matter volume of hypothalamus and left thalamus were found to be the significant predictors of trait anxiety. Our findings thus suggest that a smaller gray matter volume in the hypothalamus and an increase in the gray matter volume of left thalamus is related to a disposition to high anxiety personality trait. Graphical Abstract: Image, graphical abstract